Production and reproduction performance of cattle of irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh - M. Hanna Kumari; M. Kalyana Chakravarthi; K. Sarjan Rao; K. Sakunthala Devi; M. Muralidhar (Indian Journal of Animal Production and Management, 2022)
A study was conducted to assess the production and reproduction performance of cattle in irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh. The data pertaining to the animals of 200 dairy farmers from 50 different villages were collected by using a pretested questionnaire through personal interview and the data were analysed. The average age at first calving of graded Murrah buffaloes was significantly (P≤.01) lower in irrigated area than that in rainfed area. The mean lactation milk yield and lactation length of graded Murrah buffaloes was significantly (P≤.01) higher in irrigated area than that in rainfed area. There was no significant difference in the peak yield and dry period of graded Murrah buffaloes between irrigated and rainfed areas. The mean age at first calving of Jersey crossbred cows was significantly (P≤.01) lower in irrigated area than that in rainfed area. There was no significant difference in the service period, calving interval, peak yield, lactation milk yield, lactation length and dry period of Jersey crossbred cows between irrigated and rainfed areas.